Teacher/student perspectives and the negotiation of roles - Saroli, Anna (CIEX JOURNAL, 2015)
The scramble to keep up with the latest teaching methods and classroom tools, not to mention students’ differing expectations of their learning environment, may result in teachers feeling that they are being left behind or that their role is becoming irrelevant. This paper examines the implications for teachers of the changes in the philosophy and the practice of teaching-learning in the 21st century. After discussing some of the different perspectives on what it is to be a teacher/student/learner and looking briefly at the teacher-student relationship and how this is negotiated, it concludes by emphasizing what the central tenet of teaching should be: a focus on the student.